2010
DOI: 10.1039/c001341b
|View full text |Cite
|
Sign up to set email alerts
|

Why do crystal structures waste molecular inversion symmetry?

Abstract: Image reproduced with permission from Abbie TrewinOther articles published in this issue include:Dipyrrin based homo-and hetero-metallic infinite architectures Stéphane A. Baudron, CrystEngComm, 2010, Single-component molecular crystal structures containing centrosymmetric molecules with noncentrosymmetric crystallographic site symmetry are retrieved from the Cambridge Structural Database. The distribution amongst space group types is comparable to that for molecular crystals in general, except that there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
15
2
Order By: Relevance
“…We have previously reported a few similar examples 3638 and assume that many Z ′ > 1 structures can be interpreted in a similar fashion. The formation of crystal structures with “wasted molecular inversion symmetry” recently discussed by Bond 62 is an analogous phenomenon. The analysis of 1-I was based on a geometry comparison of its distinct molecular environments with the XPac method, which has the advantage that individual data points and molecule/molecule arrangements are intrinsically linked together.…”
Section: Discussionmentioning
confidence: 88%
“…We have previously reported a few similar examples 3638 and assume that many Z ′ > 1 structures can be interpreted in a similar fashion. The formation of crystal structures with “wasted molecular inversion symmetry” recently discussed by Bond 62 is an analogous phenomenon. The analysis of 1-I was based on a geometry comparison of its distinct molecular environments with the XPac method, which has the advantage that individual data points and molecule/molecule arrangements are intrinsically linked together.…”
Section: Discussionmentioning
confidence: 88%
“…Molecular symmetry may be benecial for close packing and it has been shown that molecules that adopt a centrosymmetric geometry in their crystal structure almost exclusively crystallise with molecules on crystallographic special positions. 38,39 However, it is not clear what role symmetry plays in determining the conformer that a molecule adopts. Here, we observe that, of the six molecules with potential centrosymmetry (FAHNOR, ODNPDS, FIBKUW, GALCAX, CELHIL SIKRIN), ve adopt centrosymmetric or nearly centrosymmetric conformations in their crystal structures.…”
Section: Which Conformation Is Adopted In a Crystal Structure? Energementioning
confidence: 99%
“…because of unrecognized crystal twinning (Herbstein, 1964). Structures with Z 0 > 1 can indicate that the crystal is actually a domain intergrowth of two or more different polymorphs (Bernstein et al, 2008;Bishop & Scudder, 2009;Bond, 2009;Bond et al, 2007;Zorky & Nesterova, 1986, 1993. Structures with high Z 0 values are often characterized by pseudosymmetry or modulation (Kuleshova et al, 2003;Schö nleber et al, 2003) and can be modified, distorted or modulated versions of the lower Z 0 structures (Bernstein et al, 2008).…”
Section: Comparison With Other Molecular Crystals Withmentioning
confidence: 99%
“…The phenomenon of the conformational polymorphism or contact conformery (the occurrence of different conformers of the same molecule in different crystal forms) has been attracting attention for a long time (see e.g. Anderson et al, 2008;Bernal, 2007;Bernstein, 1987Bernstein, , 2002Bishop & Scudder, 2009;Bond, 2010;Brock & Minton, 1989;Gavezzotti, 2008;Hao et al, 2005;Lavut et al, 1981;Leonidov et al, 1993;Nangia, 2008;Nichol & Clegg, 2007;Pidcock, 2006;Vande Velde et al, 2010;Zorky & Razumaeva, 1979). X-ray crystal structures of conformational polymorphs help to understand the interplay of intramolecular (conformer) and intermolecular (lattice) energy in the crystallization and stability of polymorphs.…”
Section: Comparison With Other Molecular Crystals Withmentioning
confidence: 99%